The Agency of Textile Technology in Some Archaeological Ritual Contexts of Northwest Argentina - Lopez Campeny, Sara Maria Luisa (2014)
I concentrate here on the agency of textiles, through certain technical features, to produce a range of social actions and effects when they intervene in the contexts of specific cultural practices. This “power” (in terms of the transformative capacity) or “magical efficacy” is made manifest visually in the textile artifacts, and they intervene in, and modify the specific social contexts in which they participate. The technical features I examine here include: the direction of thread twist, the use of contrasting tonalities and intense colors, the presence of knots, and the material basis of the textile object. These features are illustrated in a set of textile artifacts proceeding from archaeological contexts in the micro region of Antofagasta de la Sierra, in Northwest Argentina, and that cover an extended chronological sequence from about 3800 to 200 years BP. I appeal to interpretative frameworks which are supported by historical and anthropological data, and which I consider closer to the archaeological communities I am analyzing than our contemporary reality. I also take the necessary precautions so as to avoid using direct analogy, and I leave open the possibility for putting forward and checking hypotheses in specific contexts through the use of independent archaeological data.